2021
DOI: 10.1111/jace.17773
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and magnetic properties of single‐crystalline (La0.6Pr0.4)0.67Ca0.33MnO3 nanowires

Abstract: Rare earth-doped perovskite manganite oxides have promising applications in modern microelectronic devices due to their interesting electronic and magnetic properties, such as colossal magnetoresistivity (CMR), 1,2 metalinsulator transition (MIT), 3,4 nanoscale charge and orbital ordering, [5][6][7] and electronic phase separation (EPS), 8-10 because of strong couplings among the spin, orbit, charge, and lattice degrees of freedom. As a prototypical system of doped perovskite manganite oxides, the Ca-doped LaM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The sol-gel method is widely used for producing bulk perovskite manganite compounds due to its cost-effectiveness, ease of synthesis, and ability to produce homogeneous samples, as well as for allowing adjustments in transition temperatures through various element doping rates. The hydrothermal synthesis method is frequently used in the literature for the production of LBMO and BMO perovskite nanorods or nanocrystals [14]. However, it is reported that this synthesis method suffers from limitations, particularly in controlling particle size and shape, as well as achieving a homogeneous distribution due to the emergence of undesirable impurities during production [15][18].…”
Section: Introductionmentioning
confidence: 99%
“…The sol-gel method is widely used for producing bulk perovskite manganite compounds due to its cost-effectiveness, ease of synthesis, and ability to produce homogeneous samples, as well as for allowing adjustments in transition temperatures through various element doping rates. The hydrothermal synthesis method is frequently used in the literature for the production of LBMO and BMO perovskite nanorods or nanocrystals [14]. However, it is reported that this synthesis method suffers from limitations, particularly in controlling particle size and shape, as well as achieving a homogeneous distribution due to the emergence of undesirable impurities during production [15][18].…”
Section: Introductionmentioning
confidence: 99%